Enhanced thermal and dynamic mechanical properties of synthetic/natural hybrid composites with graphene nanoplateletes - Naveen, Jesuarockiam; Jawaid, Mohammad; Zainudin, Edi Syams; Hameed Sultan, Mohamed Thariq; Yahaya, Ridwan (MDPI, 2019)
The aim of the present research work is to enhance the thermal and dynamic mechanical properties of Kevlar/Cocos nucifera sheath (CS)/epoxy composites with graphene nano platelets (GNP). Laminates were fabricated through the hand lay-up method followed by hot pressing. GNP at different wt.% (0.25, 0.5, and 0.75) were incorporated with epoxy resin through ultra-sonication. Kevlar/CS composites with different weight ratios (100/0, 75/25, 50/50, 25/75, 0/100) were fabricated while maintaining a fiber/matrix weight ratio at 45/55. Thermal degradation and viscoelastic properties were evaluated using thermogravimetric analysys (TGA), differential scanning calorimetric (DSC) analysis, and a dynamic mechanical analyser (DMA). The obtained results revealed that Kevlar/CS (25/75) hybrid composites at 0.75 wt.% of GNP exhibited similar thermal stability compared to Kevlar/epoxy (100/0) composites at 0 wt.% of GNP. It has been corroborated with DSC observation that GNP act as a thermal barrier. However, DMA results showed that the Kevlar/CS (50/50) hybrid composites at 0.75 wt.% of GNP exhibited almost equal viscoelastic properties compared to Kevlar/epoxy (100/0) composites at 0 wt.% GNP due to effective crosslinking, which improves the stress transfer rate. Hence, this research proved that Kevlar can be efficiently (50%) replaced with CS at an optimal GNP loading for structural applications.